2016
DOI: 10.1093/schbul/sbw141
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Biomarkers of Schizophrenia in High Drinker Rats: A Potential Endophenotype of Compulsive Neuropsychiatric Disorders

Abstract: Psychogenic polydipsia, which is compulsive, non-regulatory fluid consumption, is present in 6%–20% of chronic psychiatric patients and frequently associated with the schizophrenia diagnosis. In the present study, we investigated the relation between schizophrenia-like symptoms and biomarkers with a compulsive drinking behavior phenotype in rats. Rats that were selected for low drinking vs high drinking behavior following schedule-induced polydipsia (SIP) were assessed in a latent inhibition (LI) paradigm usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 85 publications
4
16
0
Order By: Relevance
“…67,68 Regarding the amygdalar region, a trend toward significance was found in the BLA, indicating hyperactivity in this region, in CD compared with LD rats. In support of this, previous SIP studies found hyperactivity in serotonergic and noradrenergic neurotransmission, 14 higher binding for D2 receptors 15 in the amygdala, and less myelination of the BLA 13 in HD compared with LD rats selected by the median split. Some studies elucidating the role of the amygdala in habit formation have found that intra-amygdalar infusions of dopamine or noradrenaline agonists are sufficient to bias behavior toward the use of habit-like strategies in a water-maze task.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…67,68 Regarding the amygdalar region, a trend toward significance was found in the BLA, indicating hyperactivity in this region, in CD compared with LD rats. In support of this, previous SIP studies found hyperactivity in serotonergic and noradrenergic neurotransmission, 14 higher binding for D2 receptors 15 in the amygdala, and less myelination of the BLA 13 in HD compared with LD rats selected by the median split. Some studies elucidating the role of the amygdala in habit formation have found that intra-amygdalar infusions of dopamine or noradrenaline agonists are sufficient to bias behavior toward the use of habit-like strategies in a water-maze task.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, we cannot deduce that CD rats have an impulsive-hyperactive licking behavior like that seen in SHR rats.From all this we could conclude that the high intensity of licking is what probably best distinguished the SIP compulsive drinking, and points toward the relevance of introducing microstructural measures in studies of individual differences in SIP. We hypothesize that this excessive licking may be due to a lack of inhibition to exert control over habitual processes.In fact, previous studies that classified rats by their median water intake have shown that high-drinker rats displayed resistance to extinction in the 5-CSRT task14 and had increased lever pressing under a variable-interval 60-second schedule of reinforcement 13. These findings might indicate an increased habit formation in rats developing high-drinking rates.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In our laboratory, we have found consistent differences between these two populations in the inhibitory response deficit. Thus, HD rats selected by SIP have shown increased perseverative–compulsive responses under extinction conditions on the 5-Choice Serial Reaction Time task (5-CSRT; Moreno et al, 2012); impulsive decision making on the delay-discounting task (Cardona et al, 2011); less latent inhibition effect, considered as a behavioral model of schizophrenia, and augmented behavioral inflexibility in a spatial reversal learning task, characteristic in OCD patients (Navarro et al, 2017). Thus, HD and LD rats selected by SIP has shown consistent behavioral differences among different behavioral paradigms.…”
Section: Introductionmentioning
confidence: 99%